Algorithm of technical diagnostics of the complicated damage to the continued resource of the circulation pipeline of the nuclear power plant - Hrinchenko, H.; Trisch, R.; Burdeina, V.; Chelysheva, S. (Вопросы атомной науки и техники, 2019)
The quality and safety of operation of the main circulating pipeline of the nuclear power plant is being studied in order to extend the life of the pipelines of the reactor unit of the NPP on the basis of the development of a scientifically sound mathematical model and algorithm for their technical diagnostics. The complex estimation of the quality of operation of pipeline systems is proposed, taking into account the peculiarities of their stress-strain state and seismic stability. The purpose of the article is to substantiate the integrated assessment of the quality and safety of operation of pipelines of the reactor unit of the NPP on the basis of the development of a scientifically sound mathematical model and algorithm for their technical diagnostics in order to extend the life of the operation. Research methods: calculations by mathematical model, comparison of results of calculation, forecasting of boundary parameters of technical condition and monitoring of mechanical properties of main pipeline material, inspection, qualification, determination of residual resource of buildings, structures, foundations and metal structures taking into account geotechnical and seismotectonic conditions. It is determined that in the initial period of existence of the projected residual resource seismic activity in the zone 300...500 km from the location of the NPP is less safe than seismic activity, which takes place in the final period of the projected residual resource, as a sharp increase in the level of damage from seismic activity leads to exceeding the limit of permissible the level of damage to the material of the main pipeline.